Pemanfaatan Media dalam Kampanye Politik : Studi Kasus Analisis Akun TikTok Gerindra sebagai Sarana Kampanye Politik Prabowo – Gibran dalam Pemilu 2024 - Andini Wulan Pratiwi; Irfan Irfan (MUKASI: Jurnal Ilmu Komunikasi, 2026)
The use of social media in political campaigns increased significantly during the 2024 Presidential Election, particularly through TikTok, a platform widely used by Generation Z. this study aims to analyze the political communication strategies employed by the TikTok account of the Gerindra Party (@partaigerindra) as a campaign medium for the Prabowo Subianto–Gibran Rakabuming Raka ticket in the 2024 Presidential Election. This research adopts a qualitative approach using content analysis of 15 campaign videos uploaded between September 2023 and January 2024. The data were analyzed descriptively and interpretatively by examining content formats, narrative structures, visual symbols, and patterns of audience interaction. The findings indicate that the Gerindra Party’s TikTok account predominantly applies an edutainment-based communication strategy by combining political messages with entertainment elements such as memes, political humor, viral trends, live streaming, and influencer collaboration. These strategies aim to build emotional closeness, enhance audience engagement, and strengthen the candidates’ image among young voters. Additionally, interactive TikTok features, including comments, duets, and live streaming, facilitate two-way communication between candidates and audiences. This study concludes that TikTok functions as a strategic instrument of digital political communication, where creative, interactive, and platform-oriented content is effective in reaching and mobilizing Generation Z voters.